Fundef/Fundeb - implicações para oferta de educação infantil via convênios/ parcerias - Jaqueline dos Santos Oliveira; Raquel Fontes Borghi (EccoS – Revista Científica)
In this paper we analyze the implications of the Maintenance and Development Fund for Elementary Education and Teachers Advancement (FUNDEF) and Development Fund for Basic Education and Valuing of Education Professionals (FUNDEB) for the agreements/ partnerships extensions among the government and private institutions for the vacancies offer in Early Childhood Education. As theoretical and methodological procedure we resorted to telephone contacts with the city authorities to collect information about the partnerships/ agreements, survey and literature re-view. The data analysis was done in a qualitative way. This paper shows that during the FUNDEF period (1998-2006) the number of agreements between public and private sections increased in order that the fund favored the elementary education. We also still acknowledged the nonprofitable traditional partnerships predominance, but a considerable increase of agreements/ partnerships with profitable institutions.